PENGARUH DIGITALISASI DAN KEPEMIMPINAN TRANSFORMASIONAL TERHADAP KINERJA KARYAWAN BAGIAN OPERASIONAL PADA PT BANK CAPITAL INDONESIA - Hayati, Feb Amni; Sularmi, Lili; Veritia, Veritia; Rahmadini, Suci (Sekolah Menengah Kejuruan (SMK) Pustek, 2024)
The Influence of Digitalization and Transformational Leadership on the Performance of Operational Employees at PT Bank Capital Indonesia. The purpose of this study is to determine the influence of Digitalization and Transformational Leadership on the performance of operational employees at PT Bank Capital Indonesia. The respondents in this study amounted to 50. The data analysis in this research is quantitative, using simple linear regression and multiple linear regression methods. The data were analyzed using SPSS version 25. Based on the results of this study, it is shown that Digitalization affects the performance of operational employees at PT Bank Capital Indonesia. Transformational Leadership influences the performance of operational employees at PT Bank Capital Indonesia. Simultaneously, the variables of Digitalization and Transformational Leadership significantly influence the variable of operational employee performance at PT Bank Capital Indonesia. The R Square value is 0.609 or 60.9%, meaning that the variable of employee performance is influenced by digitalization and transformational leadership, while the remaining 39.1% is influenced by other factors not used in this study.